NOTED: Dreaded word culture 'like a newsroom hand grenade' - Danni Mulrennan (Asia Pacific Network, 2006)
They try everything, to gnaw at us, to drain us,' said the Haitaian broadcst journalist Jean Dominique. He was an enormously popular 'Mr truth' to his grassroots listeners. 'It's been going on for 50 years, and why should it stop? 'They can still try to crush us; to machinegun us; to ignore, slander bully and seduce is; to deflate, empty and distort us.'